Relation -between Nanostructural Changes and Macroscopic Effects during Reversible Temperature-Memory Effect under Stress-Free Conditions in Semicrystalline Polymer Networks. Issue 1718 (2015) - Nöchel, U.; Kratz, K.; Behl, M.; Lendlein, A.
ABSTRACT: Temperature-memory effects in polymers under stress-free conditions are typically limited to one way effects. Recently, crosslinked polymer networks comprising crystallizable domains, which were capable of a reversible temperature-memory effect (rTME) under stress-free conditions, were introduced. The utilization of crystallizable actuator domains (AD) and shape determining domains (SD) where related to two different temperature ranges of a single broad melting temperature transition in case of rTME. In this study we investigated the nanostructure of crosslinked poly[ethylene- co -(vinyl acetate)] cPEVA capable of rTME in situ during actuation cycles utilizing X-ray scattering techniques and related the changes on the nanoscale to effects on the macroscopic scale. It was observed that 23% of SD obtained at a separation temperature of 75 °C gave the highest reversible strain and when exceeding 80 °C only isotropic crystallization occurred and no rTME was observed. Furthermore, distances between oriented crystalline lamellae correlated to the macroscopic actuation during heating-cooling cycles, exhibiting long-periods from 14 to 17 nm as function of temperature.